Catheter-directed thrombolysis vs. anticoagulation for the prevention and treatment of post-thrombotic syndrome in deep vein thrombosis: An updated systematic review and meta-analysis of randomized trials. (December 2019) - Mastoris, Ioannis; Kokkinidis, Damianos G; Bikakis, Iosif; Archontakis-Barakakis, Paraschos; Papanastasiou, Christos A; Jonnalagadda, Anil Kumar; Schizas, Dimitrios; Bakoyiannis, Christos; Palaiodimos, Leonidas; Faillace, Robert T
Background: Oral anticoagulation therapy was the mainstay of deep vein thrombosis treatment but recently, catheter-directed thrombolysis has emerged as an alternative. Objective: To compare the efficacy and safety of the two strategies. Methods: Medline, Embase and Cochrane CENTRAL were reviewed. Outcomes of interest included post-thrombotic syndrome, thromboembolic events, mortality, bleeding risk and iliofemoral patency. A random effects model meta-analysis was performed. Heterogeneity was assessed with I square. Results: Four randomized controlled trials (RCTs) including 1005 patients met the inclusion criteria. Catheter-directed thrombolysis was more likely to prevent overall post-thrombotic syndrome compared to anticoagulation only (OR: 0.32; 95% CI: 0.12–0.85; I 2 =87.2%), and to lead to iliofemoral vein patency (OR: 2.7; 95% CI: 1.08–6.75; I 2 =55.3%) but no difference was noted in thromboembolic events (OR = 0.5; 95% CI: 0.08–3.02, I 2 =55.1%), bleeding and mortality rates. Conclusions: Catheter-directed thrombolysis can decrease post-thrombotic syndrome rates and improve iliofemoral vein patency compared to anticoagulation when used for the treatment of deep vein thrombosis.